Relevance of cardiac parvovirus B19 in myocarditis and dilated cardiomyopathy: review of the literature. (17th October 2016) - Verdonschot, Job; Hazebroek, Mark; Merken, Jort; Debing, Yannick; Dennert, Robert; Brunner‐La Rocca, Hans‐Peter; Heymans, Stephane
Abstract: Over the last decade, parvovirus B19 (B19V) has frequently been linked to the pathogenesis of myocarditis (MC) and its progression towards dilated cardiomyopathy (DCM). The exact role of the presence of B19V and its load remains controversial, as this virus is also found in the heart of healthy subjects. Moreover, the prognostic relevance of B19V prevalence in endomyocardial biopsies still remains unclear. As a result, it is unclear whether the presence of B19V should be treated. This review provides an overview of recent literature investigating the presence of B19V and its pathophysiological relevance in MC and DCM, as well as in normal hearts. In brief, no difference in B19V prevalence is observed between MC/DCM and healthy control hearts. Therefore, the question remains open whether and how cardiac B19V may be of pathogenetic importance. Findings suggest that B19V is aetiologically relevant either in the presence of other cardiotropic viruses, or when B19V load is high and/or actively replicating, which both may maintain myocardial (low‐grade) inflammation. Therefore, future studies should focus on the prognostic relevance of the viral load, replicative status and virus co‐infections. In addition, the immunogenetic background of MC/DCM patients that makes them susceptible to develop heart failure upon presence of B19V should be more thoroughly investigated.